Polyimide‐Based Flexible Plasma Sheet and Surface Ionization Waves Propagation (Adv. Electron. Mater. 11/2021). (10th November 2021) - Sun, Yuhao; Zhang, Bo; Wang, Chenxu; Zhang, Guanjun
Abstract : Non‐Thermal Plasma Guanjun Zhang and colleagues realize a polyimide‐based flexible sheet to generate non‐thermal plasma in atmosphere and study the propagation of ionization waves along its surface in article number 2100369 . Multiple waves propagate in a petal pattern, which is impervious to different curvature of the sheet. Bending the flexible plasma sheet will not significantly affect its utility in the fields of material processing and biomedical application.